HMGB1/IL-1β Complexes Regulate Neuroimmune Responses in Alcoholism - Coleman, Leon G. (Brain Behav Immun, 2017)
Neuroimmune activation is a key feature of the pathologies of numerous psychiatric disorders including alcoholism, depression, and anxiety. Both HMGB1 and IL-1β have been implicated in brain disorders. Previous studies find HMGB1 andIL-1β form heterocomplexes in vitro with enhanced immune responses, lead to our hypothesis that HMGB1 and IL-1β heterocomplexes formed in vivo to contribute to the pathology of alcoholism. HMGB1/IL-1β heterocomplexes were prepared in vitro and found to potentiate IL-1β receptor proinflammatory gene induction compared to IL-1β alone in hippocampal brain slice culture. These HMGB1/IL-1β complexes were found to be increased in post-mortem human alcoholic hippocampus by co-immunoprecipiation. In mice, acute binge ethanol induced both HMGB1 and IL-1β in the brain and plasma. HMGB1 and IL-1β complexes were found only in mouse brain, with confocal microscopy revealing an ethanol-induced HMGB1 and IL-1β cytoplasmic co-localization. Surprisingly, IL-1β was found primarily in neurons. Studies in hippocampal brain slice culture found ethanol increased HMGB1/IL-1β complexes in the media. These studies suggest a novel neuroimmune mechanism in the pathology of alcoholism. Immunogenic HMGB1/IL-1β complexes represent a novel target for immune modulatory therapy in alcohol use disorders, and should be investigated in other psychiatric diseases that involve a neuroimmune component.